Efek Harga Keterlambatan dan Brand Image Terhadap Kepuasan Pelanggan dalam Pilihan Jasa Pengiriman Studi Kasus PT. XYZ di Kota Bandung - Annisa Febrianti; Aam Hamdani; Saskia Kanisaa Puspanikan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of price, delivery delays, and brand image on customer satisfaction at PT XYZ. This research uses a quantitative approach with multiple linear regression analysis. Data were collected through a 5-point Likert scale questionnaire distributed online to 113 respondents who had used PT XYZ services at least twice in the past six months. The results show that price and brand image have a significant effect on customer satisfaction, while delivery delays do not have a significant effect at the 5% significance level. Simultaneously, the three variables explain 83.2% of the variation in customer satisfaction. These findings emphasize the importance of competitive pricing, operational efficiency, and a strong brand image in improving customer satisfaction.